Karakteristik Kejang Demam pada Anak di RSUD Tabanan pada Tahun 2021-2022 - Kadek Ayu Alit Sintyawati; Ni Kadek Elmy Saniathi; Luh Gde Evayanti (Fakultas Ilmu Kedokteran dan Ilmu Kesehatan, Universitas Warmadewa, 2023)
Febrile seizures are common emergency case of children between 6 months-5 years. During 2021 this cases is the most common pediatric diseases in RSUD Tabanan. Risk factors for febrile seizures in the hospitals have not been studied. This research aims to identify the characteristics of febrile seizures. This descriptive study used cross-sectional design with 145 samples selected by total sampling. Data were obtained from medical records of pediatric hospitalized in 2021-2022. The frequency distribution analysis used SPSS 25. According this study showed that febrile seizures mostly occurred in children aged 6-24 months (75.9%), predominantly in boys (62.8%) with a temperature of 38-40°C (95.2%). The most common diagnosis was simple febrile seizures (95.9%), with duration <15 minutes (95.9%), no family history of seizures (87.6%), and without recurrence (76.6%). The most common comorbid disease was acute respiratory infection (62.8%), while the lowest non-infectious disease was diabetes (0.7%). Hemoglobin and leukocyte levels were within the normal range, namely 54.5% and 75.9%. Most patients had nutritional status except good nutritional status (40.7%), did not get exclusive breastfeeding (26.9%), and had length of stay ≥3 days (82.1%). It can be concluded that febrile seizures mostly occur in boys aged 6-24 months with a temperature of 38-40°C, SFZ <15 minutes in duration is more frequent, without a history of recurrence. This seizure is commonly accompanied by ARI with normal hemoglobin and leukocyte levels. Most patients have nutritional status except good nutritional status, do not get exclusive breastfeeding, and have a length of stay ≥3 days.